Alternativas para a interoperabilidade entre sistemas de informação universitários - Sérgio Sobral Nunes (2004)
The evolution of technologies and infrastructures in the field of computer networks has brought new challenges to the organizations. Centralized systems are being replaced by distributed ones, built on top of multiple connected computers. On the other hand, from an organizational point of view, there is a greater need to access consolidated and aggregated information produced by different sources. In the case of academic institutions, where multiple power centers exist, this is a bigger issue.Thus, due to technological and organizational issues, information integration is one of the most important current challenges. In this dissertation, a study and evaluation of the major alternatives for the interoperability between university information systems is conducted.First, the concept of University Information System is presented. A brief characterization of these systems is made based on the analyses of the most common features. Then, the concept of interoperability is detailed, with a focus on the technological aspects. The major technologies and solutions related to distributed systems are reviewed here.Following this, the problem of interoperability between university information systems is presented having as an example the concrete case of the Porto University. An evaluation of the more common interaction patterns is made and the problem is structured in two axis: horizontal and vertical. Based on the description and characterization of these axis, four patterns are identified: share, aggregation, concentration and diffusion of information. Each of these patterns results in a study case, which is described and systematized with the compilation of detailed requirements.Four distinct architectures are proposed for each of the generic patterns. After being described and justified the options, a brief contextualization is made for each particular case. This work resulted in the specification of concrete solutions for the representation of data and the implementation of interaction mechanisms.In the end, several prototypes were implemented that allowed to validate the proposed solutions.